Fighting for empowerment in an age of violence - Bošković, Milica; Misev, Gordana; Putnik, Nenad (Advances in religious and cultural studies (ARCS) book series, 2022)
"This book analyzes the different forms of violence against vulnerable groups and minorities, states their civil rights, and illustrates the forms of weakening and violence supported by authorities against their own citizens by highlighting the challenges for people marked as unequal or weak and the possibilities that the 21st century offers to empower them"--